2000
DOI: 10.1177/0310057x0002800504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Incision Skin Infiltration on Post-Hysterectomy Pain—A Double-Blind Randomized Controlled Trial

Abstract: In this double-blind placebo-controlled randomized trial, we compared the analgesic effect of preoperative 0.25% bupivacaine (n=21) skin infiltration with normal saline (n=19) in patients undergoing abdominal hysterectomy through a lower midline incision. All patients received postoperative patient-controlled analgesia with morphine and were followed for 72 hours. The main outcome measures were morphine consumption and pain score at rest, and the contribution of different components of pain was also assessed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…They explained this surprising result by the fact that pain at various stages of the puerperium has been attributed to different factors. In one study of pain after abdominal hysterectomy by Leung et al, 5 the authors found that visceral pain dominated during the first 48 h after hysterectomy. The association between peritoneal stretch and uterine exteriorization can also be explained by this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They explained this surprising result by the fact that pain at various stages of the puerperium has been attributed to different factors. In one study of pain after abdominal hysterectomy by Leung et al, 5 the authors found that visceral pain dominated during the first 48 h after hysterectomy. The association between peritoneal stretch and uterine exteriorization can also be explained by this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study did not control the technique of removal of the placenta (manual or spontaneous) as it was depended on the preference of the surgeon, although there was a general agreement that the placenta not be removed manually. 5,6 To decrease the need for postoperative analgesics, considering their potential adverse effects, 8,9 especially if the woman is breast-feeding, 9 a surgical technique with less post-cesarean maternal pain is preferable. In conclusion, routine exteriorization of the uterus is associated with higher pain scores in early puerperium and it is recommended to perform in situ repair of the uterus during cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…These visceral postoperative pain scores (epigastric and global abdominal pains) were the highest in our study, while the wound pain scores were the lowest in both groups. Leung et al [17] reported that visceral pain dominated during the first 48 hours after hysterectomy. Another explanation would be a better effect of the postoperative analgesia we used to relieve the somatic pain element.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral sensitization of visceral afferents may occur due to the release of proinflammatory molecules such as bradykinin, tachykinin, and prostaglandins at the site of injury [18]. Leung et al [19] have reported that pre-incision skin infiltration of local anesthetics during hysterectomy did not contribute to postoperative analgesia, because the pain had a visceral or somatic origin. Mihic and Abram [20] reported that the optimal regional anesthesia for hysterectomy was combined spinal and epidural anesthesia, for the reason noted by Leung et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…Leung et al [19] have reported that pre-incision skin infiltration of local anesthetics during hysterectomy did not contribute to postoperative analgesia, because the pain had a visceral or somatic origin. Mihic and Abram [20] reported that the optimal regional anesthesia for hysterectomy was combined spinal and epidural anesthesia, for the reason noted by Leung et al [19]. These studies suggest that the blockade of visceral pain during and after surgery may contribute to the level of postoperative pain.…”
Section: Discussionmentioning
confidence: 99%